2011
DOI: 10.3855/jidc.1697
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter species meningitis in children: a case series from Karachi, Pakistan

Abstract: Introduction: Multidrug-resistant strains of Acinetobacter pose a serious therapeutic dilemma in hospital practice, particularly when they cause meningitis, as the few antimicrobial agents to which these isolates are susceptible have poor central nervous system (CNS) penetration. Methodology: We retrospectively reviewed the clinical course and outcome of eight consecutive cases of meningitis due to Acinetobacter spp. in children ages 15 years or less, seen in a tertiary care medical center in Karachi, Pakistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…In our study, the percentage of A. baumannii (83.33%) and other Acinetobacter species (16.67%) is found to be approximately similar in the studies by Fayyaz et al 27 and Gupta et al 29 In the present study, the percentage of Acinetobacter species in male (75.36%) and female (24.28%) is found to be approximately similar in the studies by Fayyaz et al 27 and higher than the studies by Tahseen and Talib 30 and Saleem et al 31 In our study, 1 patient was transgender admitted in pediatric ward. In the present study, the maximum frequency of Acinetobacter isolates from respiratory tract intubated patients (ET samples: 59.5%) followed by sputum (14.13%), pus swab c/s (13.40%), urine (4.35%), and blood (2.54%), which is higher than in the studies by Chim et al, 32 Markogiannakis et al, 22 and Alvarez-Lerma et al 33 In the present study, the maximum frequency of A. baumannii isolates was recovered from ICUs (63.04%) compared with wards, which is found to be similar in the studies by Xia et al 13 and Tahseen and Talib.…”
Section: Jmgumstsupporting
confidence: 83%
“…In our study, the percentage of A. baumannii (83.33%) and other Acinetobacter species (16.67%) is found to be approximately similar in the studies by Fayyaz et al 27 and Gupta et al 29 In the present study, the percentage of Acinetobacter species in male (75.36%) and female (24.28%) is found to be approximately similar in the studies by Fayyaz et al 27 and higher than the studies by Tahseen and Talib 30 and Saleem et al 31 In our study, 1 patient was transgender admitted in pediatric ward. In the present study, the maximum frequency of Acinetobacter isolates from respiratory tract intubated patients (ET samples: 59.5%) followed by sputum (14.13%), pus swab c/s (13.40%), urine (4.35%), and blood (2.54%), which is higher than in the studies by Chim et al, 32 Markogiannakis et al, 22 and Alvarez-Lerma et al 33 In the present study, the maximum frequency of A. baumannii isolates was recovered from ICUs (63.04%) compared with wards, which is found to be similar in the studies by Xia et al 13 and Tahseen and Talib.…”
Section: Jmgumstsupporting
confidence: 83%
“…The two isolates were sensitive to ampicillin-sulbactam in vitro and we used this antibiotic for treatment, but the patient did not respond to this antibiotic either. Tigecycline has in vitro activity on pan-drug resistant acinetobacter and some studies reported successful treatment of meningitis caused by multidrug resistant A. baumannii with tigecycline, yet this treatment option is very expensive and is not easily available in developing countries ( 23 , 24 ). Moreover, our isolates were susceptible to tigecycline in vitro , but tigecycline is not available in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Colistin (base) was administered intravenously at a dose of 2.5–5.0 mg (75 000–150 000 units)/kg/day in two to four divided doses, 4 mg/kg/dose twice daily via nebulisation and 0.16–0.24 mg/kg as a single daily dose via intrathecal/intraventricular route. Doses were adjusted in patients with reduced renal function 27–29. All intravenous and intrathecal doses were dispensed in prefilled ready to administer form in normal saline and infused over 30 min.…”
Section: Methodsmentioning
confidence: 99%